SQL Server 2012 T-SQL Recipes A Problem-Solution Approach - Brimhall, Jason; Dye, David; Roberts, Timothy; Sheffield, Wayne; Gennick, Jonathan; Sack, Joseph (Apress : Imprint: Apress, 2012)
SQL Server 2012 T-SQL Recipes is an example-based guide to the Transact-SQL language that is at the core of SQL Server 2012. It provides ready-to-implement solutions to common programming and database administration tasks. Learn to create databases, insert and update data, generate reports, secure your data, and more. Tasks and their solutions are broken down into a problem/solution format that is quick and easy to read so that you can get the job done fast when the pressure is on. Solutions in this book are divided into chapters by problem domain. Each chapter is a collection of solutions around a single facet of the language such as writing queries, developing triggers, and applying aggregate functions. Each solution is presented code-first, giving you a working code example to copy from and implement immediately in your own environment. Following each example is an in-depth description of how and why the given solution works. Tradeoffs and alternative approaches are also discussed. Focused on solutions: Look up what you need to do. Learn how to do it. Do it. Current: Newly updated for SQL Server 2012 Comprehensive: Covers all common T-SQL problem domains.